ANALISIS TREND POPULASI DAN PRODUKSI AYAM NIAGA PEDAGING POLA KEMITRAAN (STUDI KASUS PT CEMERLANG UNGGAS LESTARI DI KABUPATEN BANYUMAS) - Purnawan, Tofik Adri; Hidayat, Nunung Noor; Yuwono, Endro (ANGON: Journal of Animal Science and Technology, 2021)
Background. The research was conducted in Banyumas Regency on October 8, 2020 to November 20, 2020. The objectives of the study were 1) To determine the population and production of broilers in partnership patterns at PT Cemerlang Unggas Lestari, Banyumas in the last 6 years from 2014 to 2019. 2) Analyzing trends population and production of commercial broilers in partnership patterns at PT Cemerlang Unggas Lestari, Banyumas for the last 6 years from 2014 to 2019. Materials and Methods. The research was conducted using a case study sampling method at PT Cemerlang Unggas Lestari by taking data on breeders in Banyumas Regency. PT Cemerlang Unggas Lestari was selected purposively with the consideration that the company had been operating for a long time and sufficient data recording was available. The data observed were the dependent variable in the form of population trend data (Y1) and chicken production trend data (Y2) in the broiler trade in Banyumas Regency and the independent variable in the form of years (X) for the last 6 years from 2014 to 2019. The collected data were analyzed using descriptive analysis and simple statistical analysis to provide an overview of the number and average population and production of broiler chicken and the data were also analyzed using simple linear regression to determine the trend of production and population trends. Results. The results of the analysis showed that the average population of broiler commercial chickens was 1,277,346 head per year and the average production was 2,306,844 kg per year. The results of the trend analysis showed that the population trend (Y1) of broilers in the partnership pattern was Y1 = 714808 + 160725x and (R2) was 78.44% and the t-count value of 3.814 was greater than the t table of 2.776. The production trend (Y2) of broiler commercial broilers with a partnership pattern of Y2 = 1E + 06 + 279562x and (R2) of 73.41% and the t value of 3.323 is greater than the t table of 2.776. This shows that the regression line is strong enough to be used as a predictor line.